Revisão sobre pregnanos glicosídeos da subfamília Asclepiadoideae (Apocynaceae) e estudo fitoquímico e farmacológico de Mandevilla dardanoi - Lins, Francisca Sabrina Vieira (2023)
Apocynaceae, one of the largest plant families with more than 5,100 widely distributed species, serves as a significant model for evolutionary and biochemical studies. Within this family, compounds such as alkaloids, flavonoids and terpenoids with potential therapeutic activities have been isolated. Among its subfamilies, Asclepiadoideae is recognized as a rich source of C21 pregnane derivatives. Mandevilla Lindl is an important genus of the Apocynaceae family, not only as an ornamental plant, but also for its medicinal uses. In Brazil, Mandevilla species are indicated for the treatment of asthma and skin infections, and their anti-inflammatory and wound healing potential are also reported in the literature. With regard to their chemical composition, this group of plants is a notable producer of pregnane glycosides. Mandevilla dardanoi is an endemic species of the Brazilian semiarid region not studied by any phytochemical method. This research was divided into two phases, in the first a comprehensive review of pregnane glycosides (PG) obtained from Asclepiadoideae was performed, employing an interdisciplinary approach combining chemophenetics with neural network data analysis to identify promising species and bioactive compounds. For this, a dataset including 643 unique PGs and 706 botanical occurrences was compiled. Ethnopharmacological aspects as well as extraction, isolation and biological activity of PGs were analyzed and discussed. Chemophenetic analysis using self-organizing maps (SOM) and phylogenetic reconstruction revealed similarities between the tribes Marsdenia-Ceropegiae and highlighted the occurrence of the dry and diseco pregnane types, predominantly, in the tribe Asclepiadeae. Both structures showed intriguing features and their derivatives demonstrated anti-inflammatory and cytotoxic activities. Such results provide valuable information for future research on these compounds and their medicinal plant sources. Furthermore, the phylogenetic study found only one species of Mandevilla, allowing a more assertive choice of the species to be studied, with respect to the isolation of pregnanes with aglycones from differentiated skeletons. In the second phase of the study, in view of the medicinal potential of Mandevilla species, the aim was to isolate new pregnane glycosides from M. dardanoi. To achieve this main objective, modern chromatographic techniques were used. Five new pregnane glycosides, dardanols A-E, were isolated from the roots by HPLC. Their structures were determined using 1D and 2D NMR and mass spectrometry (MSn and HRESIMS) data. The cytotoxicity and anti-inflammatory potential of these compounds were evaluated by measuring pro-inflammatory cytokines and nitric oxide production by stimulated macrophages. Dardanols were able to inhibit nitric oxide production and reduce IL-1β and TNF-α. The present work demonstrates the chemodiversity of species from the Brazilian semiarid region and contributes to expand the knowledge about the biological potential of the genus Mandevilla.